The relationship between learning motivation and indonesian language proficiency among students of Syekh Abdul Halim Hasan Institute Binjai - Milfa Yetty Milfa; James Marudut; Amron Zarkasih Ritonga; Vina Rahmayanti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
Indonesian language proficiency is an important component of academic communication in higher education; however, differences in students’ abilities to use the language effectively in academic contexts are still frequently observed. One factor that is considered to influence students’ language competence is learning motivation, which encourages active engagement in the learning process. This study aims to analyze the relationship between learning motivation and Indonesian language proficiency among students at the Syekh Abdul Halim Hasan Institute, Binjai. The research employed a quantitative approach with a correlational design. A total of 30 students were selected as research participants using a simple random sampling technique. Data were collected through a learning motivation questionnaire and an Indonesian language proficiency test covering listening, speaking, reading, and writing skills. The data were analyzed using the Pearson Product–Moment correlation with the support of SPSS software. The descriptive results show that students have a relatively high level of learning motivation with a mean score of 79.80, while the mean score of Indonesian language proficiency reached 82.13, indicating good language competence. The correlation analysis revealed a positive and statistically significant relationship between learning motivation and Indonesian language proficiency (r = 0.621; p < 0.05). In addition, the analysis indicates that learning motivation contributes 38.6% to the variation in students’ language proficiency. These findings suggest that improving students’ learning motivation may support the development of their Indonesian language skills in academic settings.